Don't buy a pig in a poke: Considering challenges of and problems with performance analysis technologies in Swedish men's elite football. Issue 1 (May 2021) - Barker-Ruchti, Natalie; Svensson, Robert; Svensson, Daniel; Fransson, Dan
Abstract: During the last decades, technologies to monitor, test and analyze athletes' performance and health have rapidly developed. At present, global positioning systems (GPS), stadium camcorders, heart rate monitors and mobile applications are prominent performance analysis technologies (PATs) used in most elite sport environments. While PATs is understood as an aid, there is a growing body of literature that points to negative consequences. These negative consequences are concerning and call for research and measures to develop strategies for effective and productive implementation. To achieve this, this article first outlines key challenges and problems of PATs, using sport sociological research on coaching and athletes, historical knowledge of the scientization of training and the changing role of the coach, as well as scientific and experiential knowledge of performance analysis. Our findings show that key challenges and problems occur in a chain of six steps that concern the implementing of PATs: 1. Investment in PATs; 2. Production of performance data; 3. Interpretation of performance data; 4. Communication of performance data; 5. Decision-making based on performance data; and 6. Influence of PATs on coaches and athletes. The article then answers these challenges and problems by outlining recommendations for how sport managers and administrators can prevent buying "a pig in a poke" by acquiring competence about performance analysis and PATs, investing time, and developing effective communication between those working with PATs.